MicroRNA‐649 promotes HSV‐1 replication by directly targeting MALT1. Issue 6 (9th December 2016) - Zhang, Yi; Dai, Jun; Tang, Jinfeng; Zhou, Li; Zhou, Mengzhou
Abstract : Herpes simplex virus type 1 (HSV‐1), a member of the Herpes viridae, is associated with a wide variety of nervous system diseases including meningitis and encephalitis. The data presented here demonstrate that miR‐649 promotes the replication of HSV‐1 without affecting cell viability. Further mechanistic studies revealed that MALT1 (mucosa associated lymphoid tissue lymphoma translocation gene 1) is directly targeted by miR‐649. We then found that MALT1 and the downstream NF‐κB signaling pathway, are involved in miR‐649‐induced HSV‐1 replication. Interestingly, miR‐649 levels were downregulated after HSV‐1 infection, and miR‐649 expression was negatively associated with MALT1 expression in HSV‐1‐infected HeLa cells. Taken together, this present study indicates that miR‐649 promotes HSV‐1 replication through regulation of the MALT1‐mediated antiviral signaling pathway and suggests a promising target for antiviral therapies. J. Med. Virol. 89:1069–1079, 2017 . © 2016 Wiley Periodicals, Inc.